Multiomics analysis unveils the cellular ecosystem with clinical relevance in aldosterone-producing adenomas with KCNJ5 mutations - Maki Yokomoto-Umakoshi; Masamichi Fujita; Hironobu Umakoshi; Tatsuki Ogasawara; Norifusa Iwahashi; Kohta Nakatani; Hiroki Kaneko; Tazuru Fukumoto; Hiroshi Nakao; Shojiro Haji; Namiko Kawamura; Shuichi Shimma; et al. (Proceedings of the National Academy of Sciences, 2025)
Aldosterone-producing adenomas (APA), a major endocrine tumor and leading subtype of primary aldosteronism, cause secondary hypertension with high cardiometabolic risks. Despite potentially producing multiple steroid hormones, detailed cellular mechanisms in APA remain insufficiently studied. Our multiomics analysis focusing on APA with KCNJ5 mutations, which represent the most common genetic form, revealed marked cellular heterogeneity. Tumor cell reprogramming initiated from stress-responsive cells to aldosterone-producing or cortisol-producing cells, with the latter progressing to proliferative stromal-like cells. These cell subtypes showed spatial segregation, and APA exhibited genomic intratumor heterogeneity. Among the nonparenchymal cells, lipid-associated macrophages, which were abundant in APA, might promote the progression of cortisol-producing and stromal-like cells, suggesting their role in the tumor microenvironment. Intratumor cortisol synthesis was correlated with increased blood cortisol levels, which were associated with the development of vertebral fractures, a hallmark of osteoporosis. This study unveils the complex cellular ecosystem with clinical relevance in APA with KCNJ5 mutations, providing insights into tumor biology that could inform future clinical approaches.